Proposed development of Nusajaya Boulevard in Nusajaya Central Planning Area - Mustafa, Mohd Khairi; Said, Ismail (2007)
This project is to design and plan a boulevard at the Nusajaya Central Planning Area, the new capital city of Johor state. Nusajaya consists of a new state legislative assembly complex, the offices of the Menteri Besar and State Secretary and a state department complex. Nusajaya's overall development is planned and designed to be sustainable and conducive for business, living and leisure and this boulevard follows the same concept. In the development of a new city, the major issue is to create the identity and image of modern Johor. Moreover, it also as acts as an open space for the Nusajaya that support recreation and leisure activities in the city. According to the overall development concept, this project can act as a catalyst for the commercial activity in surrounding area. The challenge is to consider the new of all development that including human behaviour and response to the new open space for the city. The design emphasis on image of the boulevard that is shows the power and wealth in the design. The concept of this boulevard is Jalur Johor, which means a stripe that represents a multi-cultural and multi-ethnic state with rich heritage, history and iconic elements. The Jalur comprised of three major spaces: state mall, transit park and business park. This design proposal focuses on the state mall because it is the place where ceremonial event such as Independence Day, Johor Government Open House during Hari Raya and daily activities including walking, strolling and resting. It design is the Jata which means coat of arms for Johor. The main amenity in the mall is a multi functional paved area bounded by several rows of shade and large canopied trees, which gives grandiose vista effect. With the heavy-duty pavement, the parade goes from the memorial area and along the central paved area surrounded by the terrace where people can enjoy this event. The mall also comprised of a memorial area for the Sultan of Johor representing power and sovereignty. The memorial is the gateway to the state mall, which made up of arch, water features and rows of palms. The design also includes a large reflective pool that denotes the power of the sultan and it serves as recreational place. For daily activities, people can enjoy the view of water while resting at the staged area under the shade trees. The hardscape elements such as lighting pole, seating and tree grating is designed in Johor’s motifs including gambier, black pepper and Kuda kepang. These motifs portrayed the identity of the state.